Factors Affecting Corporate Income Tax Payable to Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Desfina Tristan; Latersia Br Gurusinga (Enrichment : Journal of Management, 2022)
This study aims to examine the factors that affect corporate income tax payable on property and real estate companies listed on the Indonesia Stock Exchange. The independent variables used in this study consisted of Debt Equity to Ratio, earnings management, and operational costs. The population used in this study are companies engaged in the property and real estate sector which are listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period as many as 729 companies. The total sample used is 11 companies using purposive sampling as a method for sampling. The data analysis used is multiple linear regression which includes descriptive statistical analysis, classical assumption test, and hypothesis testing. The results of the study show that partially the Debt Equity to Ratio variable and operational costs have a significant effect on the corporate income tax payable. Meanwhile, earnings management variable has no significant effect on corporate income tax payable. The independent variable explains that 51.6% can affect the corporate income tax payable, while 58.4%, the rest can be influenced by other factors not discussed in this study. In addition, simultaneously the three independent variables in this study can affect the corporate income tax payable.